The digitization of rotating parking spaces: regional platforms and the modernization of urban mobility services in the contemporary world - Barberio, Leandro Di Genova; Sugahara, Maria Carolina; Gallo, Fabricio (Geografares, 2026)
The current stage of development of information technologies allows for the exponential growth of financial transactions conducted through digital means and the implementation of new public functionalities. Thus, the objective is to contribute to the discussion of the relationship between technology’s integration into urban mobility and how it influences actions and the creation of models for monitoring on-street parking, from a new perspective of the city’s digital connection. Our methodology consists of gathering secondary data, both quantitative and qualitative, obtained from scientific articles and reports on the subject, along with fieldwork conducted in selected cities in the state of São Paulo. It is concluded that this company is positioned within the process of expanding financial services and new forms of digital payment, and that digitalization aligns with better effectiveness in extracting more revenue from public spaces.
Keywords: digitization of space; rotating parking; financialization; platforms